Arbuscular mycorrhizal fungi and soil nematodes influence the root colonisation of Araucaria angustifolia and its nutrient uptake - Souza, Tancredo; Dobner, Mario; da Silva, Lucas Jónatan Rodrigues [UNESP]; Nascimento, Gislaine dos Santos (Springer Nature, 2024)
The role of arbuscular mycorrhizal fungi (AMF) and soil nematodes in primary production and plant nutrient uptake through plant-soil feedback in the Araucaria ecosystem remains poorly quantified. We aimed to understand the role of AMF and soil nematodes on Araucaria angustifolia using three phenological stages of this native plant species: adult/mature trees in field conditions (1st experiment), from germination to the seedling stage under in situ conditions (2nd experiment), and from the seedling to sapling stage under ex situ conditions (3rd experiment). In the field experiment, we determined soil biochemical properties and AMF and soil nematode community structure. Soil inoculum was collected in the 1st experiment. Throughout the 2nd experiment, we determined plant biomass production and plant P uptake. Finally, we determined root colonisation by AMF and root lesions by root-feeding nematodes and their relationship with plant biomass and plant P content in the 3rd experiment. At the high-quality site, there was significantly higher microbial respiration, microbial N and C biomass, soil pH, soil organic carbon, total nitrogen, and Olsen’s P compared to the low-quality site. Both the in situ and ex situ stages were positively correlated with AMF diversity and negatively correlated with the abundance of root-feeding nematodes. Using structural equation modelling, we found evidence that root colonisation and root lesions were affected by AMF richness and soil nematodes. This study highlights the importance of considering the establishment of AMF and soil nematode communities, their correlation with soil quality, and Araucaria’s phenological stages (germination, seedling, sapling, and adult trees), which can be influenced by soil inoculum.
Keywords: Cambisol; Endangered tree species; Glomeromycota; P uptake by plants; Subtropical ecosystems